2020
DOI: 10.25259/sni_675_2020
|View full text |Cite
|
Sign up to set email alerts
|

“Locked up inside home” – Head injury patterns during coronavirus disease of 2019 pandemic

Abstract: Background: As citizens have been forced to stay home during coronavirus disease of 2019 (COVID-19) pandemic, the crisis created unique trends in the neurotrauma patterns with changes in mode, severity, and outcome of head injured patients. Methods: Details of neurotrauma admissions under the neurosurgery department at our institute since the onset of COVID-19 pandemic in the country were collected retrospectively and compared to the same period last year in terms of demographic profile, mode of injury, GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 19 publications
0
31
1
1
Order By: Relevance
“…Presentation delays have been reported in subarachnoid haemorrhage, cervical epidural abscess with quadriplegia, and paediatric tumour causing oedema and coma [ 23 ]. The observed increase in mortality in our study may partly be due to a delay in presentation of patients due to fear of contracting COVID-19, and other studies with increased mortality suggest this may be a contributor [ 20 , 22 ]. Initial GCS is an independent predictor of neurological outcome and mortality.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Presentation delays have been reported in subarachnoid haemorrhage, cervical epidural abscess with quadriplegia, and paediatric tumour causing oedema and coma [ 23 ]. The observed increase in mortality in our study may partly be due to a delay in presentation of patients due to fear of contracting COVID-19, and other studies with increased mortality suggest this may be a contributor [ 20 , 22 ]. Initial GCS is an independent predictor of neurological outcome and mortality.…”
Section: Discussionmentioning
confidence: 53%
“…Similarly, in patients admitted to a neurosurgical ICU in Finland with TBI or aneurysmal subarachnoid haemorrhage (SAH), no difference in mortality was seen (in either diagnosis) [ 18 ]. In contrast, a study in India reported a significant increase in neurotrauma mortality during the pandemic and attributes this to more severe injury mechanism and polytrauma [ 20 ]. An alarming trend that has become apparent is the delay in presentation and resulting worse outcomes for time sensitive emergencies such as spinal emergencies [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding outpatient services, 16.1% had completely stopped outpatient departments (OPDs), while 42.37% had switched over to telemedicine exclusively and 11.0% were doing both physical OPDs and telemedicine. We have observed reduction in OPD attendance, inpatient volumes, and surgeries performed at our center, 5 , 6 , 7 , 8 , 9 , 10 , 11 and also all over the country 12 during the ongoing pandemic. This concern has been voiced by neurosurgeons around the world.…”
mentioning
confidence: 67%
“…In our previous articles, we have raised concerns about the impact of COVID-19 pandemic on non-COVID-19 patients considered to be ” non-emergent .”[ 6 9 10 15 43 44 45 46 47 48 49 50 51 ] If postponed for too long, these patients risk presenting with more advanced diseases at a later stage. In this article, we have presented the response of our institute and neurosurgery department during the ongoing COVID-19 pandemic in an attempt to highlight our attempts to attend to the ” nonemergent ” patients along with COVID-19 and emergent cases.…”
Section: Discussionmentioning
confidence: 99%